Failure of Zr61Ti2Cu25Al12 bulk metallic glass under torsional loading. (July 2017) - Song, Zhen-Qiang; Ma, Evan; Xu, Jian
Abstract: The torsional properties of the Zr61 Ti2 Cu25 Al12 BMG have been tested using cylinder samples, including the shear yield strength, shear elastic strain limit and shear modulus. Under torsional loading, the BMG fails via a major shear band, without obvious macroscopic plasticity on the specimen surface. The shear band maintained stable propagation by a distance of ∼300 μm (∼20% of cylinder radius) before final catastrophic failure, owing to the constraint of stress gradient along the radial direction. The combined tensile, compressive and torsional properties of the Zr61 Ti2 Cu25 Al12 BMG suggest that recent ellipse criterion and eccentric ellipse criterion are more appropriate than other well-known ones in describing the yield behavior of this BMG. The cooperative shear model underestimates the shear elastic strain limit, because of its default assumption that the yielding behavior follows the Tresca yield criterion. Graphical abstract: Highlights: Torsional properties of Zr61 Ti2 Cu25 Al12 BMG were tested using cylinder samples. The BMG in torsion fails via a major shear band without visible plasticity. Shear band maintained stable propagation by a distance of ∼300 μm before failure. Ellipse and eccentric ellipse criteria are better to describe yield behavior. The cooperative shear model slightly underestimates the shear elastic strain limit.